2013
DOI: 10.6027/tn2013-526
|View full text |Cite
|
Sign up to set email alerts
|

Natural Capital in a Nordic context

Abstract: Nordic capital in a Nordic context-Status and Challenges in the Decade of Biodiversity. A study prepared by Gaia Consulting Oy and the Institute for European Environmental Policy (IEEP) for the Nordic Council of Ministers, Copenhagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…49 In Denmark two of the key areas of ecosystems are the protection and increase of forest areas and the reduction of invasive species. Iceland has sharpened its strategy to focus on invasive species, restoration of degraded habitats and conservation measures (Mazza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In Denmark two of the key areas of ecosystems are the protection and increase of forest areas and the reduction of invasive species. Iceland has sharpened its strategy to focus on invasive species, restoration of degraded habitats and conservation measures (Mazza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark one of the key areas of ecosystems are the protection and increase of forest areas and the reduction of invasive species. Iceland has sharpened their strategy to focus on invasive species, restoration of degraded habitats and conservation measures (Mazza et al, 2013). 8.3 UN SEEA experimental ecosystem accounts SEEA -Experimental Ecosystem Accounting (EEA) is an integrated statistical framework for organizing biophysical data, measuring ecosystem services, tracking changes in ecosystem assets and linking this information to economic and other human activity. SEEA EEA provides a complementary perspective to the accounting approaches described in the SEEA Central Framework (CF) but does not have the status of an international statistical standard.…”
Section: Introductionmentioning
confidence: 99%
“…This report extends and deepens the understanding of the importance of and challenges related to the sustainable management of Nordic freshwater ecosystems and the services they provide. Thus it can be seen as a continuum from previous Nordic Council of Ministers reports including Nordic Capital in a Nordic Context (Mazza et al 2013), Ecosystem Services in Nordic Freshwater Management (Magnussen et al 2014), Valuation of Ecosystem Services from Nordic Watersheds (Barton et al 2012b) and Socio-Economic Importance of Ecosystem Services in the Nordic Countries (Kettunen et al 2012). The subject and methods of the Arctic Freshwater Natural Capital project embody the themes of the Presidency and promote synergy between the Nordic's water, nature and people.…”
Section: Prefacementioning
confidence: 99%
“…Environmental evaluations, essential tools to socio-ecological system approaches (Bourgeron et al, 2018; Li et al, 2020; World Wildlife Fund, 2019), are being developed to assess the direct or indirect impacts of externalities on ecological systems and their productivity. These developments have contributed to the emergence of a broad range of approaches, methodologies and environmental evaluation instruments (Mazza et al, 2013; Organisation for Economic Co-operation and Development, 2012; United Nations Environment Programme, 2014; Weber, 2014; West, 2015), aimed to integrate the environment and natural resources into economics-based national accounting frameworks (Caldecott et al, 2013; Weber, 2018). Despite such accomplishments, a recent survey concluded that ‘there is very little use of natural capital accounts for public policy decisions and, more so, in developing countries’ (Recuero Virto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%